In vitro degradation behavior, antibacterial activity and cytotoxicity of TiO2-MAO/ZnHA composite coating on Mg alloy for orthopedic implants - Bakhsheshi-Rad, H. R. (Elsevier B. V., 2018)
Magnesium alloys as biodegradable materials have received great attention for orthopedic application as a result of their good biocompatibility, bioactivity, and mechanical properties. However, the clinical use of Mg alloys is restricted by high degradation rate. In order to reduce the degradation rate, TiO2 incorporated micro-arc oxidation (TM) coatings were prepared on Mg- Ca alloy using micro-arc oxidation (MAO). Subsequently, zinc-doped hydroxyapatite (ZH) coating was deposited by electrophoretic deposition (EPD) on the MAO coating. The electrochemical test results demonstrated that the deposition of ZH composite coatings on Mg alloy significantly reduces its corrosion rate and improves its charge transfer resistance. Antibacterial activity of the coating against Escherichia coli (E. coli) was studied using disk-diffusion and spread plate methods. The results revealed that the inhibition zone amplified after deposition of TM and ZH coatings on Mg alloy, whereas more inhibition zone was found around ZH coating. In addition, the number of E. coli colonies reduces to 92% after ZH coating implying its good antibacterial properties. The cytotoxicity test indicated that cell viability of MG63 osteoblast cells cultured with ZH extracts was higher compared to the TM coating and bare Mg alloy. These results confirm that Mg alloy coated by TM/ZH exhibits high corrosion resistance, antibacterial activity and favorable bioactivity and cytocompatibility, indicating their substantial potentials for biomedical applications.